2019
DOI: 10.1186/s12301-019-0004-3
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer awareness and attitude toward early detection among male soldiers in Ghana: a cross-sectional study

Abstract: Background: Prostate cancer (PC) is the leading cause of cancer deaths among men in Ghana. This poses a public health threat, especially among the Ghana Armed Force (GAF) where the majority are males. This study aimed to assess male soldiers' awareness, knowledge and attitudes toward early detection of prostate cancer. Results: It was found that 58.3% of the soldiers were less aware of PC and 76.0% had low or neutral knowledge regarding risk factors and symptoms of PC. The soldiers had positive attitudes towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
3
3
0
Order By: Relevance
“…Our data could support the view of a recent review study which suggested increasing high incidence of prostate cancer in younger men [27]. Our report feeding into reported low knowledge and awareness of prostate cancer risk in Ghana [28,29] call for the introduction an aggressive mass screening program to accurately detect the early detection age in the study setting.…”
Section: Resultssupporting
confidence: 87%
“…Our data could support the view of a recent review study which suggested increasing high incidence of prostate cancer in younger men [27]. Our report feeding into reported low knowledge and awareness of prostate cancer risk in Ghana [28,29] call for the introduction an aggressive mass screening program to accurately detect the early detection age in the study setting.…”
Section: Resultssupporting
confidence: 87%
“…This intention was similar when compared with another study conducted in Spain (57.9%) (11,12,13) . A similar findings are accordance with another study carried out in Jamaica, the result of study the participants had positive attitude toward early detections of prostate cancer but low intentions of getting tested (14) . This findings disagree with many studies have shown negative attitudes toward early screening for PC (15,16,17) .…”
Section: Discussionsupporting
confidence: 92%
“…The findings are not expected and therefore surprising because one expects that based on the level of education of teachers, they should be aware of prostate cancer preventive measures. The finding is in consonant with the findings of Neku et al, (2019) that 58.3% of their respondents were aware of prostate cancer preventive while 41.7% were less aware. The findings disagreed with the findings of Abdulrhman et al, (2018) that less than 30% of adult males are aware of preventive measures of prostate cancer.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…The findings were not expected and therefore surprising because it was below the researcher's expectation. Neku, et. al.…”
Section: Discussion Of Findingsmentioning
confidence: 99%